2015
DOI: 10.1111/bph.12948
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of monoacylglycerol lipase reduces nicotine withdrawal

Abstract: BACKGROUND AND PURPOSEAbrupt discontinuation of nicotine, the main psychoactive component in tobacco, induces a withdrawal syndrome in nicotine-dependent animals, consisting of somatic and affective signs, avoidance of which contributes to drug maintenance. While blockade of fatty acid amide hydrolase, the primary catabolic enzyme of the endocannabinoid arachidonoylethanolamine (anandamide), exacerbates withdrawal responses in nicotine-dependent mice, the role of monoacylglycerol lipase (MAGL), the main hydrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 56 publications
(64 reference statements)
2
25
0
Order By: Relevance
“…We next studied the consequences of the pharmacological modulation of 2-AG levels in the somatic signs of nicotine abstinence. Interestingly, the administration of the MAGL inhibitor JZL184 decreased the severity of withdrawal, as recently reported (25), while the DAGL inhibitor O7460 exacerbated these symptoms ( Figure 4A). Thus, two-way ANOVA showed an interaction between treatment and pretreatment (F3,50=13.63, p<0.05).…”
Section: Different Neurobiological Mechanisms Mediate Somatic Signs Asupporting
confidence: 85%
See 1 more Smart Citation
“…We next studied the consequences of the pharmacological modulation of 2-AG levels in the somatic signs of nicotine abstinence. Interestingly, the administration of the MAGL inhibitor JZL184 decreased the severity of withdrawal, as recently reported (25), while the DAGL inhibitor O7460 exacerbated these symptoms ( Figure 4A). Thus, two-way ANOVA showed an interaction between treatment and pretreatment (F3,50=13.63, p<0.05).…”
Section: Different Neurobiological Mechanisms Mediate Somatic Signs Asupporting
confidence: 85%
“…All drugs were administered in a volume of 10ml per kg of body weight, except for O7460 and JZL184 that were administered in 5ml/kg and 2ml/kg, respectively. Doses of the different drugs used were based on previous studies (22)(23)(24)(25).…”
mentioning
confidence: 99%
“…A well-established and validated nicotine withdrawal model was performed (Bagdas et al, 2014; Damaj et al, 2003; Muldoon et al, 2015; Salas et al, 2007) Mice were infused with 24 mg/kg/day nicotine or saline for 14 days using s.c. osmotic minipumps (model 2000; Alzet Corporation, Cupertino, CA) implanted under isoflurane anesthesia (Jackson et al, 2008). Nicotine concentration was adjusted according to animal weight and mini pump flow rate.…”
Section: Methodsmentioning
confidence: 99%
“…Fourteen days after minipump implantation, nicotine withdrawal syndrome was precipitated by the administration of the nicotinic receptor antagonist mecamylamine (2mg/kg). Systemic administration of mecamylamine in nicotine-treated rodents is a wellestablished model to study the neurobiological mechanisms involved in the different aspects that characterize the nicotine withdrawal syndrome (Muldoon et al, 2015;Qi et al, 2015;Parikh et al, 2016;Saravia et al, 2017), typically observed in abstinent smokers.…”
Section: Nicotine Treatment and Withdrawalmentioning
confidence: 99%